Composition, Predicted Functions and Co-occurrence Networks of Rhizobacterial Communities Impacting Flowering Desert Events in the Atacama Desert, Chile - Astorga-Eló, Marcia; Zhang, Qian; Larama, Giovanni; Stoll, Alexandra; Sadowsky, Michael J.; Jorquera, Milko A. (Frontiers in Microbiology, 2020)
Flowering desert (FD) events consist of the rapid flowering of a wide variety of native plants in the Atacama Desert of Chile, which is categorized as the driest desert in the world. While ephemeral plants are an integral part of the desert ecosystem, there is little knowledge on plant‒microbe interactions that occur during FD events. Consequently, the overall goals of this present study were to investigate changes in the composition and potential functions of rhizobacterial community of Cistanthe longiscapa (Montiaceae) during the 2014 and 2015 FD events and determine the composition, potential functions and co‒occurrence networks of rhizobacterial community associated with the root zone of C. longiscapa during pre‒ (PF) and full flowering (FF) phenological stages. Results of this study showed that the Proteobacteria and Actinobacteria were the dominant taxa in rhizosphere soils during the three FD events (2014, 2015 and 2017) examined. In general, greater microbial richness and diversity were observed in rhizosphere soils during the 2015-, compared with 2014-FD event. Similarly, predicted functional analyses indicated that a larger number of sequences were assigned to information processing (e.g., ion channel, transporters and ribosome) and metabolism (e.g., lipids, nitrogen and sulfur) during 2015 compared with 2014. Despite the lack of significant differences in diversity among PF and FF stages, the combined analysis of rhizobacterial community data, along with data concerning rhizosphere soil properties, evidenced differences among both phenological stages and suggested that sodium is a relevant abiotic factor shaping the rhizosphere. In general, no significant differences in predicted functions (most of them assigned to chemoheterotrophy, magnesium metabolisms and fermentation) were observed among PF and FF. Co-occurrence analysis revealed the complex rhizobacterial interactions that occur in C. longiscapa during FD, highlighting to Kouleothrixaceae family as keystone taxa. Taken together this study shows that the composition and function of rhizobacteria vary among and during FD events, where some bacterial groups and their activity impact the growth and flowering of native plants, and therefore, the ecology and trophic webs in Atacama Desert.